Analyse rétrospective de l’adaptation à la sécheresse chez le douglas - Rozenberg, Philippe; Sergent, Anne Sophie; Dalla Salda, Guillermina; Martinez Meier, Alejandro; Marin, Sara; Ruiz Diaz, Manuela; Bastien, Jean-Charles; Sanchez, Leopoldo; Bréda, Nathalie (Swiss Forestry Society and Allen Press, 2020)
For a number of years in certain regions of France the Douglas-fir trees (Pseudotsuga menziesii [Mirb.] Franco) have presented symptoms of withering which have been attributed to drought. Our results show that the hydraulic function of the wood plays a part in the resistance of the Douglas-fir to dry conditions. Narrower cellular conduits, and therefore a greater wood density, contribute to the survival of trees confronted with a period of a marked water deficit. This idea is confirmed by the existence of significant relationships between wood density and hydraulic properties of wood in which the raw sap circulates, and also by the relationships found between the ecological preferences of specimens in their area of origin and the density of their wood in regions of France where they have been introduced. Those coming from dry regions have a tendency to develop wood with characteristics similar to that of trees which have survived drought. While the relationship between wood density and survival has been demonstrated, the differences in the nature of this relationship between different sites show that the mechanisms involved are complex and to a large extent still not understood.